(untitled) - Weiss, Renée (Nerw York, 1999)
A comprehensive, flexible, and up-to-date vocabulary reference and teaching tool for English language learning. The Oxford Picture Dictionary and its components create a highly teachable programme that can be used as a complete, four-skills beginning course, or as a language development supplement and practical reference.
Keywords: English language,English language; Study and teaching,Textbooks for foreign speakers